Electrical contacts to two-dimensional transition-metal dichalcogenides. (December 2018) - Wang, Shuxian; Yu, Zhihao; Wang, Xinran
Abstract: Two-dimensional (2D) transition-metal dichalcogenides (TMDCs) have attracted enormous interests as the novel channel materials for atomically thin transistors. Despite considerable progress in recent years, the transistor performance is largely limited by the excessive contact resistance at the source/drain interface. In this review, a summary of recent progress on improving electrical contact to TMDC transistors is presented. Several important strategies including topology of contacts, choice of metals and interface engineering are discussed.